Antioxidant and renoprotective activity of 2-hydroxypropyl-β-cyclodextrin in nephrectomized rats. (9th June 2015) - Anraku, Makoto; Iohara, Daisuke; Wada, Koki; Taguchi, Kazuaki; Maruyama, Toru; Otagiri, Masaki; Uekama, Kaneto; Hirayama, Fumitoshi
Abstract: Objectives: Oxidative stress is known to be involved in the pathogenesis of chronic renal failure (CRF). In this study, the effect of cyclodextrins (CDs) on oxidative stress and CRF was investigated using 5/6 nephrectomized rats as model animals. Methods: CRF model rats were divided into five groups and treated for 8 weeks as follows: control, α-CD, β-CD, γ-CD and 2-hydroxypropyl-β-CD (HP-β-CD). Blood was collected from the rats after 4 and 8 weeks for an analysis of renal function and oxidative stress tests were carried out. Key findings: An oral administration of HP-β-CD over an 8-week period resulted in a significant decrease in serum indoxyl sulphate, creatinine and urea nitrogen levels, compared with the other CDs. The ingestion of HP-β-CD also resulted in an increase in antioxidant potential, compared with the other CDs. In in vitro studies, the interaction of HP-β-CD with a uremic toxin, indole molecule, was much higher than that for the other CDs, as evidenced by Proton nuclear magnetic resonance ( 1 H NMR) measurements. Conclusions: These results suggest that the ingestion of HP-β-CD might result in a significant reduction in the levels of pro-oxidants in the gastrointestinal tract, such as uremic toxins, thereby inhibiting the subsequent development of oxidative stress in the systemic circulation.